Synthesis of Polyesters from AB Tung Oil-based Polyol Monomers Through Step-growth Polymerization Reactions - Budiyati, Eni; Hartini, Hartini; Rochmadi, Rochmadi; Budiman, Arief; Budhijanto, Budhijanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
In this study, polyesters synthesized from AB Tung oil-based polyols (TOBPs) monomers via step-growth polymerization reactions. TOBPs are polyols made from Tung oil through a series of hydroxylation and epoxidation procedures. They have hydroxyl (OH) and carboxylic (COOH) functional groups. The polymerization was performed in a three-necked round-bottomed flask (250 mL) equipped with a magnetic stirrer, thermometer, and condenser. It is placed in an oil bath to maintain the reaction temperature. The generated moisture was collected using a vacuum pump. In the meantime, oxygen is being expelled from the reactor by nitrogen. The temperature and stirring speed were kept constant for 6 hours throughout the operation. According to the experiment, 150°C was the ideal temperature for polyesterification. The reaction rate constant rose by 4.73 to 19.99% with the addition of the p-TSA catalyst. The [COOH] and [OH] models were nearly identical to the experimental results, demonstrating the viability of the proposed kinetic model. According to the calculation's findings, polymerization without a catalyst yielded activation energies (Ea) and collision factors (A) of 27.2215 kJ/mol and 16.2965 g.mmol-1.min-1, respectively. Then, polymerization with catalyst decreased Ea and A values, which were around 26.4681 kJ/mol and 14.6746 g.mmol-1.min-1. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).